A European - Australian Comparative Study on Competency Gaps in Chef Training: Implications for Chef Training in Australia ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: This study investigates the competency gaps in chef training in Australia by comparing it with European practices. Objective: It identifies competency gaps in Australian chef training programs particularly in foundational culinary techniques, business acumen and adaptability by comparing them with European practices and propose a model for improvements based on these findings Methodology: Employing a comparative qualitative design, this study gathered data through semi-structured interviews with 29 industry professionals in Europe and Australia. Thematic analysis, based on Costa's (2019) framework and drawing on Braun and Clark's (2006) approach, was used to analyze the data. Results: Based on the findings the proposed model emphasizes practical experience, a broader curriculum and a focus on mental resilience, aiming to enhance graduate employability and meet the evolving demands of the culinary industry. Conclusion: By addressing these gaps and adopting a more holistic approach, Australian chef training programs can better equip graduates for success in the evolving culinary landscape.
Keywords: Chef training; competency gaps; graduate employability; integrative theoretical model